PENERAPAN METODE TUTOR SEBAYA UNTUK PEMBELAJARAN MATERI FUNGSI KOMPOSISI - Yuli Saputri; Ade Mirza; Hamdani Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aims to determine the  effectiveness of the application of the peer tutoring method for learning composition function material in SMAN  1 Sungai Ambawang. The research method used is descriptive method. The research subject was 24 students from class X MIPA 4 SMAN  1 Sungai Ambawang. The aspect used to determine the effectiveness of learning using the peer tutoring method was teacher’s ability in implementing learning, student learning activities and completeness of student learning outcomes. Data collection was obtained by direct observation and learning outcome test. From the results of the study it showed that the teacher’s ability (researcher) in implementing learning with the peer tutoring method was categorized good with an average of 3,45, student’s learning activities categorized active with a percentage of 75,23% and student’s outcome is not reached classical completeness with only 66,67% of student can achieve the minimum completeness criteria. The conclusion of this research is the applicaton of the peer tutoring method for learning composition function material in  class X MIPA 4 SMAN  1 Sungai Ambawang is not effective. Keywords: Peer Tutoring Method, Composition Function, Effectiveness